Artificial Versus Magneto-Aerotactic Bacterial Robots for Cancer Therapy - Sylvain Martel (Micromachines, 2026)
The use of magnetotactic bacteria (MTB), proposed by the author about 25 years ago, allowed the implementation of embedded capabilities allowing the execution of specific complex tasks such as the target delivery of therapeutics in tumoral hypoxic zones that could not be implemented in artificial micro/nanorobots due to technological limitations at such a small scale. Since then, technology has evolved but the question remains about how long such superior advantage of using only certain types of live microorganisms will last before embedding such capabilities in artificial micro/nanorobots becomes feasible while being a viable alternative. Although it is difficult to answer this question, this paper aims to provide clues with a perspective view about the challenges of implementing an artificial or synthetic counterpart by providing a general description of an equivalent artificial implementation of the embedded functional units found in such magneto-aerotactic bacterial robots for cancer therapy.